2021
DOI: 10.1039/d1lc00116g
|View full text |Cite
|
Sign up to set email alerts
|

In-flow electrochemical detection of chemicals in droplets with pyrolysed photoresist electrodes: application as a module for quantification of microsampled dopamine

Abstract: The electrochemical quantification of analytes in droplets of PBS separated by a fluorinated phase was investigated. PDMS-fused silica chips with pyrolysed photoresist electrodes were prepared using a simple fabrication technique...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…We and others have previously shown that it is possible to collect from sampling probes into nanoliter droplets, corresponding to seconds of fraction collection, that are separated by an immiscible carrier fluid. [19][20][21][22][23][24][25][26][27][28][29] Droplet microfluidics facilitates manipulation of the small samples collected and interface to analytical methods with highthroughput and mass sensitivity like chip electrophoresis, 30,31 electrospray ionization-tandem mass spectrometry (ESI-MS/ MS), 32,33 inductively coupled plasma-mass spectrometry (ICP-MS), 34 electrochemical sensors, 22 and luminescence assays 24 to achieve temporal resolution of seconds.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that it is possible to collect from sampling probes into nanoliter droplets, corresponding to seconds of fraction collection, that are separated by an immiscible carrier fluid. [19][20][21][22][23][24][25][26][27][28][29] Droplet microfluidics facilitates manipulation of the small samples collected and interface to analytical methods with highthroughput and mass sensitivity like chip electrophoresis, 30,31 electrospray ionization-tandem mass spectrometry (ESI-MS/ MS), 32,33 inductively coupled plasma-mass spectrometry (ICP-MS), 34 electrochemical sensors, 22 and luminescence assays 24 to achieve temporal resolution of seconds.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet generation using microfluidics is a well-known, established technique and has many applications in chemical and biological sciences [ 16 ]. Several new and improved methods have been reported to generate droplets and have demonstrated applications in developing different biological assays [ 17 , 18 , 19 ]. A microfluidics-based strategy was combined with a DNAzyme sensor to detect E. coli (E. coli K12) from unprocessed blood samples [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This benefitted from the rich literature of droplet microfluidics (e.g., droplet generation 28 , picoinjection 29 , phase extraction [30][31][32] , etc.). These solutions, which were extensively covered in recent reviews [33][34][35][36] , comprise in-flow electrochemical chips 37,38 , fluorescent assays 23,39,40 and include many developments of electrophoretic 30,41 and mass spectrometry methods 26,[42][43][44][45][46][47][48] .…”
Section: Introductionmentioning
confidence: 99%